Investigation of self-propulsion of DARPA Suboff by RANS method. (15th February 2018) - Sezen, Savas; Dogrul, Ali; Delen, Cihad; Bal, Sakir
Abstract: In this study, the resistance and self-propulsion analyses of the benchmark DARPA Suboff with E1619 propeller have been done using Computational Fluid Dynamics (CFD) method. Single phase analyses have been carried out by assuming 3-D, turbulent, incompressible and steady flow, thus the governing equations (RANS Equations) have been discretized with finite volume method (FVM). First, verification and validation studies have been carried out in order to determine the optimum grid numbers for resistance analyses of bare and appended forms, and then for open water propeller analyses. The numerical studies have been done by taking the propeller-hull interaction into consideration by two methods for different velocities. First, the propeller has been modeled as an actuator disc based on body force method coupled with the experimental open water data. The propeller itself has later been modeled behind the hull with a rotating region. Performance analyses have been carried out at the self-propulsion points determined by these two methods. Self-propulsion characteristics have been estimated using thrust identity method. Finally, a comprehensive investigation of wake has been carried out by comparing the present results with those of other studies and the applicability of CFD on self-propulsion prediction of the underwater vehicles has been discussed. Highlights: The quasi propeller coefficient is higher for self-propelled case (with E1619 propeller) than that of body force method. Appendages cause slight increase in wake coefficients and thrust deduction factors. This CFD methodology predicts the V-shape carving in wake field that is compatible with experiments.